2012
DOI: 10.1016/j.jtcvs.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of modified ultrafiltration in adults undergoing coronary artery bypass grafting is associated with inflammatory modulation and less postoperative blood loss: A randomized and controlled study

Abstract: Use of MUF was associated with increased inflammatory response, reduced blood loss, and less blood transfusions in adults undergoing coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
0
28
0
4
Order By: Relevance
“…Torina et al reported that MUF decreased amount of surgical bleeding and use of blood products postoperatively, but did not make any difference in pulmonary parameters. Also, MUF was not effective for improving the inflammatory response and decreasing the ICU or hospitalization periods [11]. In their study, Kosouret al stated that no statistically significant difference was present in pulmonary parameters between the control and ultrafiltration applied groups [12].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Torina et al reported that MUF decreased amount of surgical bleeding and use of blood products postoperatively, but did not make any difference in pulmonary parameters. Also, MUF was not effective for improving the inflammatory response and decreasing the ICU or hospitalization periods [11]. In their study, Kosouret al stated that no statistically significant difference was present in pulmonary parameters between the control and ultrafiltration applied groups [12].…”
Section: Discussionmentioning
confidence: 89%
“…Processing the blood by cell salvage or ultrafiltration (UF) increases the hematocrit and hemoglobin levels [5,10]. Also, UF removes the excess water, cytokines, toxins, concentrate coagulation factors, decreases tissue edema and inflammatory response to CPB [11,12]. By the time, different UF techniques were developed such as "Conventional UF (CUF)" which is applied during CPB via a haemofilter inserted into the bypass circuit, "Modified UF (MUF)" which is applied after CPB, before protamine administration with blood removed from arterial line and returned to the venous line after passing through the haemofilterand "Zero-balanced UF (Z-BUF)" in which a balanced electrolyte solution is given as much as the volume taken [13].…”
Section: Introductionmentioning
confidence: 99%
“…Для попередження постперфузійних ускладнень та поліпшення перебігу післяопераційного періоду, особливо в дитячій кардіохірургії, використовують різні методики УФ крові [18,19]. Сприятливий ефект даного методу слід розглядати, як наслідок прямого видалення потенційно шкідливих сполук через синтетичну пористу мембрану, у результаті чого утворюється ультрафільтрат, який складається з речовин з молекулярною масою менше 50 000 [14, [18][19][20]. Але у дорослих пацієнтів вплив УФ на зниження медіаторів запалення вивчено недостатньо.…”
Section: результати дослідженняunclassified
“…Так, кілька досліджень впливу УФ крові під час ШК показали здатність даної методики знижувати IL 6, IL 8, TNF-α та молекули адгезії лейкоцитів, але не було помітних клінічних відмінностей [14,20]. У іншому дослідженні також було продемонстровано зниження вмісту цитокінів (IL 1, IL 6 та TNF-α ) через 6 годин після УФ, але не було впливу на плазмовий рівень IL 8 [21].…”
Section: результати дослідженняunclassified
“…It does not appear to be entirely due to the amount of volume removed [52]. It has been suggested that modified UF in the context of cardiac surgery reduces levels of inflammatory cytokines, but this has not been proven for acutely decompensated HF [53]. It is possible that relief of congestion, however it is achieved, will allow greater efficacy of loop diuretics, and that UF is simply a more direct way to achieve this; the efficacy of UF is not (necessarily) dependent on renal function.…”
Section: Future Perspectivesmentioning
confidence: 99%